(untitled) (Nigerian Journal of Technology, 2017)
Thermal stability of transitional alumina phases produced from ammonium alum using Kankara kaolin as starting material was studied. Wet beneficiation method was employed to purify the starting material, after which it was calcined and dealuminated with sulphuric acid. The elemental composition, mineralogical, and physiological analyses were carried out using X-ray fluorescence (XRF), X-ray diffraction (XRD) and Brunauer-Emmett-Teller (BET) techniques respectively. The ammonium alum was thermally treated by varying the calcination temperature from 700 to 1200°C and varying the time of calcination from 1 to 4 h. The formation of gamma alumina began at calcination temperature of 825°C for calcination time of 3 h, which was found to be lower than reported works of 900°C. It was found to be stable at higher temperature of 1125°C, above which phase transformation to alpha alumina was observed. The observed wide range of thermal stability of the gamma alumina phase gives it good advantage to be used for high temperature applications, such as support for catalyst promoters. Alpha alumina phase formation began at 1150°C and was fully formed at 1200°C. BET specific surface area of 166 m2/g was obtained for the gamma alumina phase which was high enough for it application as support for catalyst, catalyst and adsorbent. http://dx.doi.org/10.4314/njt.v36i3.23